IMPLEMENTASI SUDUT KEBAIKAN UNTUK MENINGKATKAN PERILAKU POSITIF SISWA SEKOLAH DASAR - Shofy Haifa' Mahdiyyah; M. Bambang Edi Siswanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to describe the implementation of the Kindness Corner and analyze its contribution in improving positive behavior of elementary school students. This study used a descriptive qualitative method with observation and documentation techniques that were carried out for one month in grades III A and III B. Initial observations showed that some students were not accustomed to writing down the positive actions they did, so that a habituation media was needed that could help students recognize and practice good behavior in a more directed manner. Data were analyzed through the process of reduction, presentation, and drawing conclusions. The results showed an increase in student participation in recording good actions, as seen from the increase in the number of checkmarks in the kindness journal between October and November. Students also showed increased enthusiasm for writing daily acts of kindness and began to understand the importance of their positive actions. Furthermore, students began to demonstrate positive behaviors more regularly in their daily classroom activities, such as helping friends, maintaining cleanliness, obeying rules, and showing concern for the learning environment. Through independent recording activities, students had the opportunity to engage in simple reflection on their behavior. These findings suggest that the Kindness Corner can be an effective visual medium for supporting the development of good behavior in elementary school students and helping strengthen character development through simple, structured, and easily implemented activities in the classroom.